Bond strength of glass fiber posts using different endodontic treatments - Robinsom Viégas Montenegro; Nathalie Murielly Rolim Abreu; Priscilla Kelly Batista da Silva Leite; Raquel Venâncio Fernandes Dantas; Ana karina Maciel de Andrade; André Ulisses Dantas Batista (Editorial Ciencias Médicas, 2020)
Introduction: Glass fiber posts have been widely used for the reconstruction of elements with excessive dental structure loss. Objective: Evaluate the bond strength of glass fiber posts after various root dentin treatments in different regions (cervical, middle and apical thirds). Methods: An experimental in vitro study was conducted. Forty bovine teeth were selected, prepared and distributed into four groups according to the surface treatment used: (1) adhesive, (2) chelating agent, (3) polyacrylic acid, (4) not treated. The glass fiber posts were cemented with self-etch resin cement. After 20 days, each root was sectioned crosswise into three slices (1 mm in thickness) obtained from three regions. Bond strength was determined in each section with a push-out bond strength test. Flexural strength data (MPa) were analyzed with ANOVA and Tukey's tests. Results: In the cervical portion, the group with previous polyacrylic acid treatment displayed lower push-out strength than the group without previous treatment. The group with application of the adhesive system (28.89 ± 6.64 MPa) and the group with previous EDTA treatment (21.58 ± 6.39 MPa) did not exhibit any statistically significant differences in comparison with the group without previous treatment (control group) in the cervical third. In the middle and apical portions, the group treated with the adhesive Ambar® of FGM Dental Group showed higher bond values in comparison with the other groups. Conclusion: Previous adhesive application increased bond strength in the middle and apical thirds in comparison with the other groups, and may thus have a beneficial effect on the clinical success of the restorative treatment.